Distribute first:
2x-6x+24=-4
which simplifies to:
-4x+24=-4
Move the constants to one side:
-4x=-28
Divide:
x=7
2006-12-03 10:12:57
·
answer #1
·
answered by Steady As She Goes 2
·
0⤊
0⤋
7
2006-12-03 10:14:17
·
answer #2
·
answered by ranchan_black17 2
·
0⤊
0⤋
initiate by increasing the 4 by the parenthesis, then bypass all words of x on one aspect of the equation, and each and every thing else to the different, then you could sparkling up for x: -2x + a million = 4(x + 3) -2x + a million = 4x + 12 -6x = 11 x = -11/6
2016-11-30 02:37:16
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
The answer is 7
2x-6x+24=-4
-4x= -28
28/4 = 7
2006-12-03 10:20:31
·
answer #4
·
answered by kit_e_kat 2
·
0⤊
0⤋
7
2006-12-03 10:13:58
·
answer #5
·
answered by b_dubs_3030 2
·
0⤊
1⤋
x = 7
2006-12-03 10:13:25
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
x= 7
2006-12-03 11:25:57
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
2x - 6x + 24 = -4
-4x + 24 = -4
-4x = -28
x = 7
2006-12-03 10:15:52
·
answer #8
·
answered by xgravity23 3
·
0⤊
0⤋
2x - 6x + 24 = -4
-4x = -28
x = 7
2006-12-03 18:53:02
·
answer #9
·
answered by mad_integer 3
·
0⤊
0⤋
2x-6(x-4)=-4
2x-6x+24=-4
-4x=-28
x=7
2006-12-03 10:14:10
·
answer #10
·
answered by Hera 2
·
0⤊
1⤋